(3bHhd Gh QaV GdYdGL h GKQg Ydi GdeSDdjI GdeOfjI (B: s (3OQGSI ebGQfI (B/ s - (3YHOGdfHi YHOGdSejY YWG Gddg TMGJgs; (3eMeO TcQi SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3dG eQGA ef Gf LSe GdGfSGf gh Pdc GdegHW GdeGOi ddMjGI PGJgG (B: (3agh YHGQI Yf eLehYI ef GdGYVGA GdJi JJhdi GdhXGFa GdMjhjI HGdfSHI dHbGA GdGfSGf ShGA cGfJ gPg GdhXGFa ef Pdc GdfhY GdaSjhdhLi Gh ef GdfhY GdYbdi hGdfaSjs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B569-590s
Keywords: (3GdbGfhf GdeOfjs; (3GdYdGLs; (3GdYed GdWHjs; (3GdhXGFa GdMjhjIs; (3GdYbO GdWHjs; (3bHhd Ch QaV GdYdGLs; (3GdGdJRGe HJHUjQ GdeQjVs; (3GdeUdMI GdYdGLjIs; (3QVGA GdeQjVs; (3GdMGdGJ GdeQVjI GdejFhS ef TaGFgGs; (3eYGdLI GdeQjVs; (3fbd hRQY GdCYVGA s; (3GdJLGQH GdWHjIs; (3YedjGJ GdJdbjM s; (3fbd GdOes; (3GdELgGVs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs